Enhancing Competitiveness in Sri Lanka - World Bank Group (World Bank, Washington, DC, 2016)
Sri Lanka needs to address new challenges if it is to sustain its strong record of economic growth and poverty reduction. The country has in many respects been a development success story, with average growth exceeding 6 percent and a threefold decline in poverty using the national poverty line over the past 10 years. However, low productivity, high reliance on non-tradable sectors and a stale export basket highlight the need to enhance private sector competitiveness as a way to create one million new jobs. The Government of Sri Lanka (GoSL) has recognized the need to adopt a policy agenda that strengthens the competitiveness of the country’s private sector in order to achieve inclusive and sustainable growth. The new Government has emphasized the need to realize Sri Lanka’s trade potential as a way to accelerate the transformation of the economy and generate new and more attractive opportunities for Sri Lanka’s labor force.Unleashing the competitiveness potential of Sri Lankan enterprises will require addressing a wide range of factors. this note focuses on opportunities to improve areas directly impacting the competitiveness of the private sector, including streamlining the regulations governing the activities of the private sector to reduce the cost of doing business; strengthening trade policies to eliminate biases against exports; enhancing trade facilitation to reduce the costs and time it takes to export; enhancing the ability of the country to attract, retain and integrate FDI; enhancing innovation and entrepreneurship and strengthening accessibility to financial services. It is important to note, that there are small islands of Research and Development (R&D) progress in Sri Lanka. Going forward, as Sri Lanka aspires to become a higher middle income economy driven by higher addedvalue exports, major reforms will be required in its investment climate; investment, innovation andtrade policies and the efficiency of the institutions governing the activities of domestic and foreign firms.This note summarizes the main findings of this work and outlines options forimplementation of reforms needed.